Pareto Distributions Second Edition - Arnold, Barry C. 1939- (CRC Press, 2015)
Historical Sketch with Emphasis on Income Modeling Introduction The First Steps The Modern Era Models for Income Distributions What Is a Model? The Law of Proportional Effect (Gibrat) A Markov Chain Model (Champernowne) The Coin Shower (Ericson) An Open Population Model (Rutherford) The Yule Distribution (Simon) Income Determined by Inherited Wealth (Wold-Whittle) The Pyramid (Lydall) Competitive Bidding for Employment (Arnold and Laguna) Other Models Parametric Families for Fitting Income Distributions Pareto and Related Heavy-Tailed Distributions Introduction The Generalized Pareto Distributions Distributional PropertiesOrder Statistics Record Values Generalized Order Statistics Residual Life Asymptotic Results Characterizations Related Distributions The Discrete Pareto (Zipf) Distribution Remarks Measures of Inequality Apologia for Prolixity Common Measures of Inequality of Distributions Inequality Statistics Inequality Principles and Utility Optimal Income Distributions Inference for Pareto Distributions Introduction Parameter Estimation Interval Estimates Parametric Hypotheses Tests to Aid in Model Selection Specialized Techniques for Various Data Configurations Grouped Data Inference for Related Distributions Multivariate Pareto Distributions Introduction A Hierarchy of Multivariate Pareto Models Alternative Multivariate Pareto Distributions Related Multivariate Models Pareto and Semi-Pareto Processes Inference for Multivariate Pareto Distributions Multivariate Discrete Pareto (Zipf) Distributions Appendix A: Historical Income Data Sources Appendix B: Two Representative Data Sets Appendix C: A Quarterly Household Income Data Set References Subject Index Author Index
Description based on publisher supplied metadata and other sources
Keywords: Mathematisches Modell; Wirtschaft; Distribution (Probability theory); Economics -- Statistical methods; Income distribution -- Mathematical models